CSF1R inhibitors induce a sex-specific resilient microglial phenotype and functional rescue in a tauopathy mouse model - Noah R. Johnson; Peng Yuan; Erika Castillo; T. Peter Lopez; Weizhou Yue; Annalise Bond; Brianna M. Rivera; Miranda C. Sullivan; Masakazu Hirouchi; Kurt Giles; Atsushi Aoyagi; Carlo Condello (Nature Communications, 2023)
Tau-mediated neurodegeneration is driven by disease-activated microglia and suppressed by their pharmacological blockade. The authors identified drug dose- and sex-dependent residual microglial phenotypes, neuronal excitotoxicity, and animal survival.